DETERMINAN KEPUTUSAN PENGGUNA DENGAN MEDIASI VARIABEL KEPERCAYAAN: STUDI KASUS PENGGUNA QRIS DI KOTA BOGOR - Nuryanto, Guyub; Harmadi, Ashur (STKIP Persada Khatulistiwa Sintang, 2025)
The public chooses digital services based on factors considered when selecting a digital payment system. Due to the convenience offered, transaction services using the Quick Response Code Indonesian Standard (QRIS) method have become increasingly popular. This study aims to analyze and identify the determinants of the decision to use QRIS, mediated by the trust variable among QRIS users in Bogor City. The analytical method used is primary data described from quantitative data obtained through online questionnaire distribution. This study employs a quantitative research approach with purposive sampling. Based on the predetermined criteria, 125 respondents were obtained, and data analysis was conducted using SmartPLS 4.0 software. The study's findings are as follows: Perceived ease of use influences the decision to use QRIS. Perceived usefulness influences the decision to use QRIS. Perceived ease of use does not influence trust. Perceived usefulness influences trust. Trust influences the decision to use QRIS. Perceived ease of use does not influence the decision to use QRIS through trust. Perceived usefulness influences the decision to use QRIS through trust. The variable with the strongest influence on the decision to use QRIS is perceived ease of use.